A Proposed Model of Community Environmental Education Program Development - Wijarn, Lawan (Naresuan University Journal: Science and Technology (NUJST), 2020)
Objective: To propose a feasible model of community environmental education program development. Method: The research was implemented in two phases. Phase 1 developed a structured interview form according to the researcher’s model of community environmental education program development which comprised of 7 steps. This form was used to interview 3 experts who were highly experienced in developing the program. The experts’ consistent opinions were used to create a rating scale questionnaire to use in gathering 19 experienced experts’ opinions on the model in phase 2. Phase 2 applied the Delphi Technique to collect 19 experts ’opinions by using the rating scale questionnaire created from phase 1 through 2 rounds of questionnaire. The results showed that, in general, experts had consistent opinions and were most agreed with every step of the proposed model of community environmental education program development. Therefore, it could be concluded that the proposed model was a feasible model of community environmental education program development.         This shows that the experts Most of them have a consensus that the model steps are feasible to make Project participants have learned to Community real environmental problems, causes of community environmental problems, and guidelines to prevent and solve environmental problems that people in the community can actually do. Which is the main objective of presenting all environmental education projects in the community. In addition, the implementation of this model can also be applied to other project planning, for example, it is used for agricultural career development. Allowing project participants to learn until they can bring their knowledge to a career as well. Keywords: Program Development, Delphi technique, Community Environmental Education